2011
DOI: 10.1021/ja207882h
|View full text |Cite
|
Sign up to set email alerts
|

Rapid C–H Bond Activation by a Monocopper(III)–Hydroxide Complex

Abstract: One electron oxidation of the tetragonal Cu(II) complex [Bu4N][LCuOH] at −80 °C generated the reactive intermediate LCuOH, which was shown to be a Cu(III) complex on the basis of spectroscopy and theory (L = N,N′-bis(2,6-diisopropylphenyl)-2,6-pyridinedicarboxamide). The complex LCuOH reacts with dihydroanthracene to yield anthracene and the Cu(II) complex LCu(OH2). Kinetic studies showed that the reaction occurs via H-atom abstraction via a second-order rate law at high rates (cf. k = 1.1(1) M−1s−1 at −80 °C,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
202
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(223 citation statements)
references
References 44 publications
17
202
0
2
Order By: Relevance
“…Tolman and co-workers synthesized a LCu III -OH complex generated by one electron oxidation of corresponding LCu II -OH (L: N,N 0 -bis(2,6-diisopropylephenyl)-2,6-pyridinedicarboxamide). 37 The synthetic Cu III -OH complex can react with dihydroanthracene (DHA) to yield a dominant anthracene product with the reduced Cu(II) complex (Scheme 22), and the kinetic studies revealed that the reaction occurs via a hydrogen atom transfer pathway with a very large KIE value (44 at 203 K).…”
Section: Hydrogen Abstraction Reactivity Of the Active Metal Hydroxo mentioning
confidence: 99%
“…Tolman and co-workers synthesized a LCu III -OH complex generated by one electron oxidation of corresponding LCu II -OH (L: N,N 0 -bis(2,6-diisopropylephenyl)-2,6-pyridinedicarboxamide). 37 The synthetic Cu III -OH complex can react with dihydroanthracene (DHA) to yield a dominant anthracene product with the reduced Cu(II) complex (Scheme 22), and the kinetic studies revealed that the reaction occurs via a hydrogen atom transfer pathway with a very large KIE value (44 at 203 K).…”
Section: Hydrogen Abstraction Reactivity Of the Active Metal Hydroxo mentioning
confidence: 99%
“…In a different approach, monocopper-hydroxide complexes 99 (R ¼ iPr or Me) were shown to undergo 1-electron oxidation at low potential (for R ¼ iPr, À0.076 V versus ferrocenium/ferrocene (Fc + /Fc) in acetone) to yield highly colored reactive intermediates ( Figure 47) [323,324]. These intermediates were identified as Cu(III)-hydroxide species 100 on the basis of DFT calculations and X-ray absorption spectroscopy for the system with R ¼ iPr [323].…”
Section: Cuoor Complexesmentioning
confidence: 99%
“…These intermediates were identified as Cu(III)-hydroxide species 100 on the basis of DFT calculations and X-ray absorption spectroscopy for the system with R ¼ iPr [323].…”
Section: Cuoor Complexesmentioning
confidence: 99%
“…The second characteristic set of ligands is {NH 2 ,2×N -,N im }. In this series (10)(11)(12)(13)(14), the slope approximates the 59 mV/logβ(Cu II ) unit value, which, in turn, means a nearly unchanged logβ Cu(III) . We found that complex 13 from this group was twice as active in water oxidation electrocatalysis as 9.…”
Section: Relating the Cu(iii)/cu(ii) Formal Potentials To The Differementioning
confidence: 92%
“…The feasibility of this option could be judged from the reactivity of the prepared species toward substrate C-H bonds. [11,12] Utilization of suitable tridentate pyridine-or piperidine-2,6-dicarboxamide-type supporting ligands provided LCu(III)-OH complexes from the LCu (II)-OH 2 precursors with 1e -oxidant, highlighting a new avenue to reactive high-valent copper species (Scheme 1b). [13,14] These substances possess hydroxide as a fourth equatorial ligand and their reactivity against C-H compounds exhibiting different bond dissociation energies (BDEs) extends to tetrahydrofurane and cyclohexane.…”
Section: Mononuclear Cu(iii) Complexesmentioning
confidence: 99%